Penggunaan Multiple Account Instagram di Kalangan Generasi Z (Studi Kualitatif Deskriptif Siswa Kelas XI Tahun Pelajaran 2022/2023 SMK Negeri Nusawungu) - Mutiara Gustyan Ayuni; Diana Khuntari; Marwan Marwan (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The development of social media has transformed the way Generation Z constructs and presents their self-identity. One emerging phenomenon is the use of more than one Instagram account by a single user, known as the first account and second account. This study aims to analyze the use of multiple Instagram accounts by Generation Z in shaping self-image, using Erving Goffman's dramaturgical theory. This research adopts a descriptive qualitative method with a phenomenological approach. The informants consisted of eight 11th-grade students from SMK Negeri Nusawungu who actively used multiple Instagram accounts. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that the first account functions as the front stage, where informants present an ideal image with curated content and carefully managed impressions. In contrast, the second account serves as the back stage, used for freer, more spontaneous, and emotional self-expression, with a more selective and private audience. The seven key dramaturgical concepts—mystification, setting, front personal, role distance, stigma, impression management, and frame analysis—were identified in the online behavior of the informants. This study recommends the importance of digital literacy and social empathy in understanding the dynamics of youth identity in digital spaces.